Virtual Reality (VR) As E-Commerce Platform To Expand SMES Market In Nusa Tenggara Timur - Arya Brehaspati Adisasmito; Achmad Ghazali (Syntax Literate, 2022)
Sustainable Development Goal (SDG) has been a global scale movement to fulfill the 2030 zero poverty agenda, Institut Teknologi Bandung, in presence of the Research and Community Service Campus's Institution (The LPPM) annually perform certain funding for community service action in order to fulfill SDGs agenda, and also as the duty of the higher education (Tridharma Perguruan Tinggi), the LPPM annually sent teams of lecturers and students to solve issues in the society across the country's rural region. A technology adoption project in the city of Kupang has been made, Kupang as the capital city of Nusa Tenggara Timur (NTT) province, a far east region of Indonesia, is a nice place for experiment on modifying locals behavior that are far from the nation's capital, Jakarta. The province holds a significant problem, which is low GDP and limited market, also undeveloped product management that devalue its price. The project implemented design thinking process scheme, one of which is utilizing recent virtual technology on providing digital space on e-commerce activity, 15 Small Medium Enterprises (SME) under the province's creative committee (The Dekranasda) has been chosen, the SME were provided with a 3D profile in the VR platform.